The Neapolitan School of Fencing: Its Origins and Early Characteristics - Blair Charles (Bern Open Publishing, 2014)
The Neapolitan school of fencing, which received official sanction after the reunification of Italy in the nineteenth century, originated in the seventeenth century. It was originally best known as a system of sword and dagger fencing. It is documented as such in both Italian and Spanish sources during the reign of Carlos II and the War of the Spanish Succession (1665-1714). This article discusses the evidence from both sets of sources during this period, comparing and contrasting the Neapolitan approach to previous, contemporary and subsequent approaches in order to provide the necessary historical context for its origin and development.